The Impact of Transformational Leadership Style, Organizational Citizenship Behavior, and Work Satisfaction on A Galuh Protank Logistics Group’s Employees’ Performance - Retno Purwani Setyaningrum (Wacana Journal of Social and Humanity Studies, 2018)
This research is aimed to study the influence of transformational leadership and organizational citizenship behavior (OCB) implementation on employee performance and aimed to study the influence of transformational leadership and organizational citizenship behavior (OCB) implementation on job satisfaction and the subsequent effect of job satisfaction on employee performance. Employee performance is the primary factor in the achievement of company goals. This research will answer these problems: (1) Does transformational leadership affect employee performance? (2) Does job satisfaction affect employee performance? (3) Does transformational leadership affect employee performance as mediated by employee job satisfaction? (4) Does the OCB affect employee performance? (5) Does the OCB affect employee performance as mediated by employee job satisfaction? This research follows a quantitative approach using data that was gathered through questionnaires. The population of this research are Galuh Protank Logistics Group employees. Forty-eight employees were respondents. SEM-PLS Warps test was used to analyze the data. The research results indicate that the influence of transformational leadership and OCB on employee performance is significant, but the influence of job satisfaction on employee performance is not significant. The research results indicate that the influence of transformational leadership and OCB on employee job satisfaction is significant.Keywords: Employee performance, Job satisfaction, Organization Citizenship Behavior, Transformational leadership style